1997
DOI: 10.1016/s0006-3495(97)78856-8
|View full text |Cite
|
Sign up to set email alerts
|

Two distinct gating mechanisms in gap junction channels: CO2-sensitive and voltage-sensitive

Abstract: The chemical gating of single-gap junction channels was studied by the dual whole-cell voltage-clamp method in HeLa cells transfected with connexin43 (HeLa43) and in fibroblasts from sciatic nerves. Junctional current (Ij), single-channel conductance, and Ij kinetics were studied in cell pairs during CO2 uncoupling and recoupling at small transjunctional voltages (Vj < 35 mV: Vj gating absent) and at high Vj (Vj > 40 mV: Vj gating strongly activated). In the absence of Vj gating, CO2 exclusively caused Ij slow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
104
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 111 publications
(112 citation statements)
references
References 24 publications
7
104
0
Order By: Relevance
“…Analogous to the TSF system of Harris et al (37) or the excised patch experiments of Verselis et al (38), this is a reductionist system. We limit the number of variables in the imaging experiment, which makes our results complementary to the pH studies done in whole cells (12,39). We have found that Cx26 hemichannels close in response to acidification, but only in the presence of an aminosulfonate buffer, suggesting that the aminosulfonate cation acts as a modulator or ligand to specific sites on the Cx26 protein.…”
Section: Discussionmentioning
confidence: 66%
“…Analogous to the TSF system of Harris et al (37) or the excised patch experiments of Verselis et al (38), this is a reductionist system. We limit the number of variables in the imaging experiment, which makes our results complementary to the pH studies done in whole cells (12,39). We have found that Cx26 hemichannels close in response to acidification, but only in the presence of an aminosulfonate buffer, suggesting that the aminosulfonate cation acts as a modulator or ligand to specific sites on the Cx26 protein.…”
Section: Discussionmentioning
confidence: 66%
“…At least two voltage sensitive gates have been identified: fast and slow. The fast gate and chemical gate are believed to be distinct, whereas slow gate and chemical gate are likely to be the same (Bukauskas and Peracchia, 1997;Peracchia et al, 1999Peracchia et al, , 2000. Slow and fast V j gates are in series and each hemichannel appears to have both gates.…”
Section: B Effects Of Cftr Expression On Cx45 Voltage-sensitivity Anmentioning
confidence: 99%
“…It has been shown that gating of GJ channels by voltage is predominantly between the open state and a long-lived substate; the V j gating transitions are fast and typical of ion channel gating and complete closures are infrequent (11,12). However, complete closures can be induced by exposure to chemical uncouplers, such as H + or alkanols (13). The transitions associated with chemical gating are slow, taking tens of milliseconds to complete, are common to cell-cell channels formed of all connexins and resemble the gating transitions induced by low pH in Cx46 hemichannels.…”
Section: Acidification-induced Transitions Varied Frommentioning
confidence: 99%